2016
DOI: 10.1097/spv.0000000000000246
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Chronic Mesh Infection in Delayed-Onset Vaginal Mesh Complications or Recurrent Urinary Tract Infections

Abstract: In this large cohort of patients with mesh removed for a diverse array of complications, cultures of the explanted vaginal mesh demonstrate frequent low-density bacterial colonization. We found no differences in culture results from women with delayed-onset pain versus acute pain, vaginal mesh extrusions versus no extrusions, or recurrent UTIs using standard culture methods. Chronic prosthetic infections in other areas of medicine are associated with bacterial biofilms, which are resistant to typical culture t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 27 publications
0
12
1
2
Order By: Relevance
“…Prevalence rates of UTI at 1 year after surgery in the present study were 20.9% for the TVT‐obturator group and 23.3% for the TVT‐abbrevo group. These rates were lower than those previously reported for UTI after midurethral sling procedures . No episodes of bladder injury occurred during the present study period and approximately 90% of the participants were satisfied with the surgical results.…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations
“…Prevalence rates of UTI at 1 year after surgery in the present study were 20.9% for the TVT‐obturator group and 23.3% for the TVT‐abbrevo group. These rates were lower than those previously reported for UTI after midurethral sling procedures . No episodes of bladder injury occurred during the present study period and approximately 90% of the participants were satisfied with the surgical results.…”
Section: Discussioncontrasting
confidence: 67%
“…Previous studies suggest that UTI is a much more common and troublesome adverse events following midurethral sling procedures than groin pain (20%–30% vs 1%–12%, respectively); however, UTI has been scarcely studied. The present study found no difference in rates of long‐term postoperative UTI between the two groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…New areas of research are being explored, including the possibility that pain is associated with infection of the mesh. 30 Patient concern/anxiety surrounding surgical mesh An unconventional postoperative "complication" that we have noted in our practice is the presentation of patients with postoperative anxiety regarding surgical mesh. Despite extensive efforts at providing informed consent preoperatively, some patients become uneasy with the use of surgical mesh and wish to have it removed.…”
Section: Painmentioning
confidence: 99%